A Dual‐Functional Metallogel of Amphiphilic Copper(II) Quinolinol: Redox Responsiveness and Enantioselectivity. Issue 9 (16th January 2013) - Miao, Wangen; Zhang, Li; Wang, Xiufeng; Cao, Hai; Jin, Qingxian; Liu, Minghua
Abstract A dual‐functional metallogel, which was based on the copper(II) complex of quinolinol‐substituted L‐glutamide, showed both redox‐responsive and enantioselective properties; moreover, the metallogels collapsed into a sol after reduction and could be revived upon subsequent oxidation. The supramolecular chirality and morphology also reversible changed with the gel–sol transition. Furthermore, the metallogels showed new enantioselective recognition towards chiral aromatic amino acids. A new emission band in the blue‐light region at around 393 nm appeared when the metallogels encountered L‐aromatic amino acids, whereas no new emission band was observed for the corresponding D‐aromatic amino acids. Such enantioselectivity only occurred in the gel state. No similar phenomenon could be observed in solution. This result suggested that, during the gel formation, the gelator molecules self‐assembled into ordered, chiral supramolecular structures and enhanced the enantiorecognition of the L‐aromatic amino acids.